Treating cachexia using soluble ACVR2B improves survival, alters mTOR localization, and attenuates liver and spleen responses. Issue 3 (2nd May 2018) - Nissinen, Tuuli A.; Hentilä, Jaakko; Penna, Fabio; Lampinen, Anita; Lautaoja, Juulia H.; Fachada, Vasco; Holopainen, Tanja; Ritvos, Olli; Kivelä, Riikka; Hulmi, Juha J.
Abstract: Background: Cancer cachexia increases morbidity and mortality, and blocking of activin receptor ligands has improved survival in experimental cancer. However, the underlying mechanisms have not yet been fully uncovered. Methods: The effects of blocking activin receptor type 2 (ACVR2) ligands on both muscle and non‐muscle tissues were investigated in a preclinical model of cancer cachexia using a recombinant soluble ACVR2B (sACVR2B‐Fc). Treatment with sACVR2B‐Fc was applied either only before the tumour formation or with continued treatment both before and after tumour formation. The potential roles of muscle and non‐muscle tissues in cancer cachexia were investigated in order to understand the possible mechanisms of improved survival mediated by ACVR2 ligand blocking. Results: Blocking of ACVR2 ligands improved survival in tumour‐bearing mice only when the mice were treated both before and after the tumour formation. This occurred without effects on tumour growth, production of pro‐inflammatory cytokines or the level of physical activity. ACVR2 ligand blocking was associated with increased muscle (limb and diaphragm) mass and attenuation of both hepatic protein synthesis and splenomegaly. Especially, the effects on the liver and the spleen were observed independent of the treatment protocol. The prevention of splenomegaly by sACVR2B‐Fc was not explained by decreased markers of myeloid‐derived suppressor cells. Decreased tibialis anterior, diaphragm, and heart protein synthesis were observed in cachectic mice. This was associated with decreased mechanistic target of rapamycin (mTOR) colocalization with late‐endosomes/lysosomes, which correlated with cachexia and reduced muscle protein synthesis. Conclusions: The prolonged survival with continued ACVR2 ligand blocking could potentially be attributed in part to the maintenance of limb and respiratory muscle mass, but many observed non‐muscle effects suggest that the effect may be more complex than previously thought. Our novel finding showing decreased mTOR localization in skeletal muscle with lysosomes/late‐endosomes in cancer opens up new research questions and possible treatment options for cachexia.